La comunera as a producer : Women's work for men's work - De la Cadena, Marisol (1985)
This article has two parts: the first is a proposal for the analysis of the role of women in the economy and in the peasant social organization, in the second the reader is offered the analysis of a case study, using to the extent of the elements mentioned in the first part as much as possible. We did not use them in their entirety since the data that make up the case study were not collected within the context of a specific investigation on peasant women.